Optimization of Physical Fitness of Children with Intellectual Disabilities Through Physical Activities - Awaliyyah, Ulfatul Azizah; Junaidi, Said; Irawan, Fajar Awang (Universitas Negeri Semarang, 2025)
Physical fitness is defined as the body's ability to perform daily physical activities without feeling excessively tired. This study aimed to determine the contribution of physical activity to physical fitness in children with intellectual disabilities in Semarang. This study used a correlational research type and a purposive sampling technique. The sample criteria in this study included children with special needs classified as intellectual disabilities with an IQ of 50-70 in grades 4, 5, and 6 of elementary school-aged 10-12 years with a total of 50 students. This research instrument used a physical activity questionnaire Physical Activity Questionnaire for Children (PAQ-C) and physical fitness using the Indonesian Student Fitness Test (TKSI) for intellectual disabilities. Data analysis used SPSS version 26 with normality, linearity, and Pearson correlation tests. The study’s results found that a significant value of 0.000 <0.05 and a Pearson correlation value of 0.243 had a positive relationship and a fairly strong relationship level and contributed 25.9% of physical activity to physical fitness. The higher the physical activity, the more positive impact it will have on the physical fitness of children with intellectual disabilities in Semarang. Physical activities such as aerobic exercise programs that are designed to be fun and interactive can increase participation in physical activity and physical fitness in children with intellectual disabilities. Further research suggestions can add analysis to other variables that affect physical fitness such as diet, sleep quality, and stress levels to provide a deeper understanding.